Powers of pilgrimage: Religion in a world of movement - Coleman, Simon (New York New York University Press, 2021)
This book offers a new theoretical framework for exploring contemporary pilgrimage, exploring examples ranging from the Hajj to the Camino, and arguing that pilgrimage activity should be understood not solely as going to, staying at, and leaving a sacred place, but also as occurring in apparently mundane or domestic times, places, and practices.